2020
DOI: 10.1017/s0022215120000833
|View full text |Cite
|
Sign up to set email alerts
|

Acute mastoiditis in children: contemporary opportunities and challenges

Abstract: BackgroundMastoiditis is the most common intra-temporal complication of acute otitis media. Despite potentially lethal sequelae, optimal management remains poorly defined.MethodA retrospective case review was conducted of children diagnosed with mastoiditis at a tertiary referral centre, in North East England, between 2010 and 2017.ResultsFifty-one cases were identified, 49 without cholesteatoma. Median patient age was 42 months (2 months to 18 years) and median hospital stay was 4 days (range, 0–27 days). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 22 publications
2
15
0
Order By: Relevance
“…A median age of 3.2 years in period 1 was significantly younger than the 4.7 years in period 2. The pre‐COVID‐19 figure is comparable to a recent UK series, 17 though older than most large International cohorts (1.3–2.1 years) 11,12,19 . In line with our hypothesis, Camanni et al found children aged 5–9 years were most commonly affected by mastoiditis in the summer, and an association between older age and P. aeruginosa as a causative organism for mastoiditis is described 16,18 …”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…A median age of 3.2 years in period 1 was significantly younger than the 4.7 years in period 2. The pre‐COVID‐19 figure is comparable to a recent UK series, 17 though older than most large International cohorts (1.3–2.1 years) 11,12,19 . In line with our hypothesis, Camanni et al found children aged 5–9 years were most commonly affected by mastoiditis in the summer, and an association between older age and P. aeruginosa as a causative organism for mastoiditis is described 16,18 …”
Section: Discussionsupporting
confidence: 88%
“…Camanni et al reported cases of paediatric mastoiditis limited to summer months (June‐September), finding P. aeruginosa to be the most commonly isolated organism, accounting for 51.6% of positive samples 16 . Our study did not collect data from the preceding summer to compare with period 2 unfortunately, and it is noted that P. aeruginosa can be prominent in some multi‐year series 17,18 …”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations